Combined effects of a circuit training programme and honey supplementation on immune functions in young males - Mohamed, Husna Afifah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
INTRODUCTION: Besides physical activity, immune level can be enhanced and maintained through adequate nutritional intake. To date, little is lmown about combination effects of exercise and honey supplementation on immune functions in young males. PURPOSE: This study was carried out to investigate the effects of a combined circuit training programmne and honey supplementation on immune functions in young males. METHODS : Forty young male subjects were assigned into four groups, with ten subjects per group (n=lO): sedentary without honey supplementation control (C), sedentary with honey supplementation (H), circuit training programme without honey supplementation (Ex), circuit training programme with honey supplementation (HEx) groups. Circuit training programme was performed by the subjects three times per week for six weeks. Tualang Honey was consumed by the subjects at a dosage of20 g diluted in 300 ml of plain water per day, seven days per week for six weeks in (H) and (HEx) groups. Subjects in (HEx) consumed honey drink 30 minutes before performing exercise. Immediately before six weeks of experimental period, subjects' anthropometry parameters were measured. Blood samples were taken before and after experimental period in order to measure white blood cells, lymphocytes, monocytes, basophil, and natural killer cells to determine the level of immune functions. RESULTS: There were no significant changes in white blood cells and lymphocytes in C, H, Ex and HEx groups. In H, Ex and HEx, there were significant higher INTRODUCTION: Besides physical activity, immune level can be enhanced and maintained through adequate nutritional intake. To date, little is lmown about combination effects of exercise and honey supplementation on immune functions in young males. PURPOSE: This study was carried out to investigate the effects of a combined circuit training programmne and honey supplementation on immune functions in young males. METHODS : Forty young male subjects were assigned into four groups, with ten subjects per group (n=lO): sedentary without honey supplementation control (C), sedentary with honey supplementation (H), circuit training programme without honey supplementation (Ex), circuit training programme with honey supplementation (HEx) groups. Circuit training programme was performed by the subjects three times per week for six weeks. Tualang Honey was consumed by the subjects at a dosage of20 g diluted in 300 ml of plain water per day, seven days per week for six weeks in (H) and (HEx) groups. Subjects in (HEx) consumed honey drink 30 minutes before performing exercise. Immediately before six weeks of experimental period, subjects' anthropometry parameters were measured. Blood samples were taken before and after experimental period in order to measure white blood cells, lymphocytes, monocytes, basophil, and natural killer cells to determine the level of immune functions. RESULTS: There were no significant changes in white blood cells and lymphocytes in C, H, Ex and HEx groups. In H, Ex and HEx, there were significant higher